Analisis Arsitektur Bisnis Sistem Penerimaan Mahasiswa Baru dan Akademik - Tiur Gantini; Adelia Adelia; Diana Trivena Yulianti; Joshia Yeremia; Novia Roro Dorojatun (Maranatha University Press, 2020)
Abstract — University in Bandung already has an IT Blueprint in 2009 and has successfully implemented several integrations in the financial system for academics. However, until 2020 there was no integration between the new student admission system and the academic system. Therefore, through this research, preparation and analysis were carried out to then proceed with the design in order to gradually document the IT Blueprint. And on this occasion discussed the preparation and analysis of the new student admission system and the academic system. The framework used is TOGAF 9.1 and TOGAF 9.2, namely in the preparation stage to phase B Architecture Vision. This research has been conducted from June 2019 to August 2020 and has produced a Value Chain Diagram, Stakeholder Map, and Solution Concept Diagram which will become the basis for phase B. The resulting Value Chain Diagram consists of the Value Chain Diagram for the admission system and the Value Chain Diagram for the academic system. In each diagram discusses the main activities and support activities of each system. The stakeholder map will explain each stakeholder involved in the admission system and the academic system and their relationship to architectural design. The Solution Concept Diagram illustrates the concept diagram as a solution architecture vision for admission and the academic system at University. Keywords— analysis; Enterprise Architecture; preliminary, Architecture Vision, TOGAF